Posisi Media Televisi dalam Membangun Nilai-Nilai pada Masyarakat Perbatasan - Petrus Ana Andung; Dian Wardiana Sjuchro; Aloysius Liliweri; Purwanti Hadisiwi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
The presence of television within the border communities of Indonesia-Timor Leste in Napan Village (Timor Tengah Utara District, East Nusa Tenggara Province) has many influences on their daily life. The high penetration of television in their daily life makes them to rely on television both regarding content (TV program) as well as technological (physical) aspects. This research aims to analyze the position of television in building the values in the daily life of the people of Napan Village. Using media ethnography method, this research found that television has a central position in this society. Widespread of Indonesia’s television broadcasting program in the border areas of Indonesia becomes one of the factors that can foster to the national pride of the Napan people. Besides, possessing a television becomes one of important determinants of comfort in household audience. Television for the people of Napan Village also has economic value as a tool to help running their business in the border area in Timor Leste. The high penetration of television has also made television programs as one of the topics in daily conversation. The television schedule has become a community schedule.